Disrupted Brain Connectivity Patterns in Patients with Type 2 Diabetes - Cui, Y.; Li, S.-F.; Gu, H.; Hu, Y.-Z.; Liang, X.; Lu, C.-Q.; Cai, Y.; Wang, C.-X.; Yang, Y.; Teng, G.-J. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Type 2 diabetes is associated with an increased risk of dementia. This study investigated the global connectivity patterns in the brains of patients with type 2 diabetes by using a functional MR imaging technique.MATERIALS AND METHODS: Forty patients and 43 age-, sex-, and education-matched healthy controls underwent resting-state functional imaging in a 3T MR imaging unit. Degree centrality, a commonly used measurement of global connectivity, was computed for a full-brain exploration of the regions influenced by type 2 diabetes. We then examined the functional connectivity of each region by using the seed-based approach. Finally, voxelwise correlation analyses were performed to explore the relationship among the connectivity changes, cognitive performance, and diabetes-related variables.RESULTS: Patients exhibited decreased degree centrality in the left lingual gyrus and increased centrality in the right insula and dorsal anterior cingulate cortex (corrected P < .05). The occipital network anchored in the lingual gyrus showed extensively reduced connectivity, while the network connectivity of the insula and cingulate cortex (mostly included in the salience network) was significantly elevated (corrected P < .05). Correlational analyses revealed that in the diabetic group, impaired visual memory and executive function performance were correlated with occipital hypoconnectivity, while higher fasting plasma glucose levels and better executive functioning were related to anterior cingulate cortex hyperconnectivity (all corrected P values < .05). Similar effects were not detected in the controls.CONCLUSIONS: This preliminary study shows that network connectivity is altered in patients with type 2 diabetes, which may provide critical insight into the neural substrate of diabetes-related cognitive decline.CFTComplex Figure TestdACCdorsal anterior cingulate cortexDCdegree centralityFCfunctional connectivityFPGfasting plasma glucoseHbA1cglycosylated hemoglobinHChealthy controlT2DMtype 2 diabetes mellitusTMTTrail-Making Test